Peta Sebaran Luas Tanam Padi per Kecamatan di Kabupaten Pati Tahun 2024 - Moh Zaenal Fanani; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Pati Regency in Central Java is one of the major contributors to rice production, where agricultural activities play an important role in supporting regional food security. This study aims to visualize the distribution of rice planting areas by sub-district in Pati Regency in 2024 using a Geographic Information System (GIS). The research method involved the collection and processing of spatial and non-spatial data, digitization of administrative boundary maps, and the creation of thematic maps using QGIS software. The results indicate that the thematic map provides a clearer, more effective, and informative visualization of rice planting area distribution patterns compared to conventional tabular data. This spatial visualization is expected to assist stakeholders and policymakers in analyzing agricultural conditions and supporting decision-making related to agricultural planning and land management in Pati Regency.